Comparing the Effects of Early Versus Late Exercise Intervention on Pain and Neurodynamic Mobility Following Unilateral Lumbar Microdiscectomy: A Pilot Study. Issue 18 (15th September 2021) - LeBlanc, Lorraine; Moldovan, Ioana D.; Sabri, Elham; Phan, Philippe; Agbi, Charles; Mohammed, Safraz; AlKherayf, Fahad
Abstract : Study Design: A pilot, two-group pretest–posttest randomized controlled, single blinded study. Objective: Our study aim was to compare the changes in low back pain level, fear avoidance, neurodynamic mobility, and function after early versus later exercise intervention following a unilateral lumbar microdiscectomy. Summary of Background Data: Exercise is commonly recommended to patients following a lumbar microdiscectomy although controversy remains as to the timing and protocols for exercise intervention. Methods: Forty patients were randomly allocated to early (Group 1) or later (Group 2) exercise intervention group. The low back pain and fear avoidance were evaluated using Oswestry Low Back Pain Disability Questionnaire, Numeric Pain Rating Scale, and Fear-Avoidance Beliefs Questionnaire. The neurodynamic mobility and function were recorded with Dualer Pro IQ Inclinometer, 50-foot walk test, and Patient-Specific Functional Scale. Two-sided t test for continuous variables and chi-square or Fisher exact test for categorical variables were used to compare the two groups' demographic data. The Wilcoxon signed-rank and rank-sum tests were used to compare the changes and the differences, respectively, in low back pain, fear avoidance, neurodynamic mobility, and function between baseline (before surgery) and postoperative repeated measurements (at 1–2, 4–6, and 8–10 wks after surgery) within each study group, after exercise intervention. Results: Both groups showed a significant decrease in low back pain levels and fear avoidance as well as a significant improvement in neurodynamic mobility and function at 4 and 8 weeks after surgery. However, no significant difference was reported between the two groups. Conclusion: Our study results showed that early exercise intervention after lumbar microdiscectomy is safe and may reduce the low back pain, decrease fear avoidance, and improve neurodynamic mobility and function. A randomized controlled trial is needed to evaluate the early exercise intervention's effectiveness after lumbar microdiscectomy, and thus validate our findings. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textPostoperative low back pain, fear avoidance, and mobility impairments persist in some patients following lumbar microdiscectomy. The study results showed a significant decrease in low back pain levels and fear avoidance as well as a significant improvement in neurodynamic mobility and function after specific early exercise intervention following lumbar microdiscectomy.